Masjid Raya Al-Ma’shun sebagai Objek Wisata Religi di Kota Medan - Daulay, Rukiyah; Siregar, Syahruddin; Nurhayani, Nurhayani (Medan Resource Center, 2024)
This research examines Al-Ma'shun Grand Mosque in Medan City as a religious tourism object. The background of this research is the importance of this mosque not only as a place of worship, but also as a tourist destination that attracts many local and international visitors. The main research question is how Al-Ma'shun Grand Mosque functions as a religious tourist attraction and what impact it has on tourism in Medan City. The research method used is a qualitative approach with data collection techniques through interviews, observation, and document analysis. The results showed that Al-Ma'shun Grand Mosque has a unique architectural appeal and high historical value, which makes it one of the main destinations for religious tourists. The conclusion of this study is that Al-Ma'shun Grand Mosque plays a significant role in increasing religious tourism in Medan, and more intensive preservation and promotion efforts can increase the tourism potential of this mosque. This research makes an important contribution in understanding the role of mosques as religious tourism objects and their impact on local tourism development.